TRANSFORMING TOURISM COMMUNICATION: THE IMPACT OF DIGITAL ADVANCEMENTS AND AI INTEGRATION - Kusumanegara, Idris; Sjuchro, Dian Wardiana; Nurfauziah, Isni; Nugraha, Aditia (ASPIRATION Journal, 2024)
This research explores the dynamic interplay between tourism and communication, with a specific focus on the influence of digital advancements, including AI-powered tools, on tourism communication within a descriptive qualitative approach and literature study framework. Research Issues: The primary research issue addressed in this study pertains to the impact of digital advancements and AI integration in descriptive qualitative approach and literature study-based tourism communication. Communication Philosophy: A dialogical communication philosophy is adopted, emphasizing meaningful engagement between tourism providers and travelers. Communication Paradigm: The study aligns with a constructivist communication paradigm, recognizing the co-creation of meaning in tourism communication. This research underscores the significance of collaborative efforts among government agencies, travel industry stakeholders, travelers, and academics to fully utilize AI's potential in enhancing qualitative tourism communication. The study's findings are anticipated to benefit all stakeholders in tourism communication by improving efficiency and personalization, ultimately contributing to the industry's growth and sustainability.